2020
DOI: 10.32674/jis.v10i3.1231
|View full text |Cite
|
Sign up to set email alerts
|

Seeking to Understand the Impact of Collaboration on Intercultural Communication Apprehension

Abstract: To assess the impact of collaboration on intercultural communication apprehension (ICA), this mixed-methods study compared ICA levels of 41 domestic and international undergraduates who participated in collaborative activities with 79 students in a control group. International student participants came from a variety of countries, while the majority of domestic students were White. A Mann-Whitney U test was used to determine if there were differences in Personal Report of Intercultural Communication Apprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Jacobi (2020) stated that exposure to different cultures would certainly provide an opportunity to trigger familiarity and communication to take apprehension under control. However, it was suggested that avoiding intercultural communication, which incites apprehension, increases the uncertainty and, therefore, is ineffective in reducing apprehension (Neuliep, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Jacobi (2020) stated that exposure to different cultures would certainly provide an opportunity to trigger familiarity and communication to take apprehension under control. However, it was suggested that avoiding intercultural communication, which incites apprehension, increases the uncertainty and, therefore, is ineffective in reducing apprehension (Neuliep, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, people should live in an assortment of societies, and their perspectives, convictions, and practices from what they have procured can't be pertinent to all civic establishments (Chen, 2010). As a response, people should track down a way to separate themselves from different gatherings to suit the principles and practices of the new friendly and social setting (Darwish, 2015;Jacobi, 2020). Before it was endured and ready to connect with different gatherings as an endurance adaption in the public arena (Croucher, 2013).…”
Section: Introductionmentioning
confidence: 99%